Pengembangan Perangkat Pembelajaran dalam Gamitan Efektivitas Membaca Berorientasi Strategi DRTA di kelas VI Sekolah Dasar - Faisal , (Prosiding Seminar Nasional Jurusan PGSD FIP UNP Tahun 2015, 2015)
This was a developmental research which was intended to develop valid, practical, and effective DRTA strategy-oriented reading instructional materials in class VI of Elementary School which involve syllabus, Lesson Plan, and learning materials. The instructional materials were developed by using 4-D model (Defining, Designing, Developing, and Disseminating). The disseminating phase, however, was done in a limited scale. The design was validated by three experts and three educational practitioners. To see the practicality and the effectiveness of the materials developed, it then was tried out limitedly to the students in class VI of SD Negeri 10 Lembah Melintang. Based on the result of the research, it was concluded that the DRTA strategy-oriented reading instructional materials developed had been valid, practical, and effective.